Investigating greenhouse gas dispersions and energy consumptive in tea cultivation - Yıldız, Taner (Emirates Journal of Food and Agriculture, 2023)
Abstract: The study aimed to uncloak use efficiency of energy and greenhouse gas dispersions in tea cultivation. The study was performed in Rize Province of Türkiye in 2021. In the study, the energy input-output, specific energy, net energy, energy productivity, energy efficiency, types of energy input; greenhouse gas emission, and greenhouse gas emission rates were calculated. A proportional sample survey was used to assess the number of enterprises to be studied for survey and data studies, and face-to-face interviews were held in 2021 with 103 enterprises that could be reached. In the study, energy input was 25686.59 MJha-1, output of energy as 10633.04 MJha-1, efficiency of energy as 0.41, specific energy as 1.93 MJkg-1, productivity of energy as 0.52 kgMJ-1, net energy as -15053.55 MJha-1. 48.72% of all the inputs used in production consisted of human labor energy by 12513.35 MJha-1, 34.40% consisted of the energy of chemical fertilizers by 8835.67 MJha-1, 10.02% consisted of diesel fuel by 2573.37 MJha-1, 4.41% consisted of electricity by 1134 MJha-1, 2.22% consisted of machinery by 570.40 MJha-1 and 0.23% consisted of transportation by 59.81 MJha-1. 63.15% (16220 MJha-1) of the inputs consisted of direct 36.85% (9465.88 MJha-1) and consisted of indirect energy, 48.72% (12513.35 MJha-1) consisted of renewable energy and 51.28% (13173.24 MJha-1) consisted of non-renewable energy. Total greenhouse gas dispersion and greenhouse gas dispersion ratio have been respectively calculated as 551.82 kgCO2-eqha-1 and 0.04 kgCO2-eqkg-1. Keywords: Energy consumption; GHG dispersion; GHG ratio; Tea; Türkiye